The Role of Pericytes in Inner Ear Disorders: A Comprehensive Review - Antonino Maniaci; Marilena Briglia; Fabio Allia; Giuseppe Montalbano; Giovanni Luca Romano; Mohamed Amine Zaouali; Dorra H’mida; Caterina Gagliano; Roberta Malaguarnera; Mario Lentini; Adriana Carol Eleonora Graziano; Giovanni Giurdanella (Biology)
Inner ear disorders, including sensorineural hearing loss, Meniere’s disease, and vestibular neuritis, are prevalent conditions that significantly impact the quality of life. Despite their high incidence, the underlying pathophysiology of these disorders remains elusive, and current treatment options are often inadequate. Emerging evidence suggests that pericytes, a type of vascular mural cell specialized to maintain the integrity and function of the microvasculature, may play a crucial role in the development and progression of inner ear disorders. The pericytes are present in the microvasculature of both the cochlea and the vestibular system, where they regulate blood flow, maintain the blood–labyrinth barrier, facilitate angiogenesis, and provide trophic support to neurons. Understanding their role in inner ear disorders may provide valuable insights into the pathophysiology of these conditions and lead to the development of novel diagnostic and therapeutic strategies, improving the standard of living. This comprehensive review aims to provide a detailed overview of the role of pericytes in inner ear disorders, highlighting the anatomy and physiology in the microvasculature, and analyzing the mechanisms that contribute to the development of the disorders. Furthermore, we explore the potential pericyte-targeted therapies, including antioxidant, anti-inflammatory, and angiogenic approaches, as well as gene therapy strategies.